Contextual meaning in Juvenal - Van Ryneveld, Louis Felix (University of the Free State, 1983)
Abstract not available
Keywords: Juvenal. The satires -- Criticism and interpretation; Latin poetry -- History and criticism; Dissertation (M.A. (Latin))--University of the Free State, 1983